Effect of Bufalin-PLGA Microspheres in the Alleviation of Neuropathic Pain via the CCI Model - Long, Lina; Zhong, Wenwei; Guo, Liwei; Ji, Jing; Nie, Hong (Frontiers in Pharmacology, 2022)
The treatment of neuropathic pain (NPP) is considered challenging, while the search for alternative medication is striving. NPP pathology is related with the expression of both the purinergic 2X7 (P2X7) receptor and transient receptor potential vanilloid 1 receptor (TRPV1). Bufalin is a traditional Chinese medication derived from toad venom with pronounced anti-tumor, analgesic, and anti-inflammatory properties. However, poor solubility, rapid metabolism together with the knowledge gap on its pain alleviation mechanism have limited the clinical application of bufalin. Hence, the purpose of this study is to illustrate the NPP alleviation mechanism of bufalin via chronic constriction injury (CCI). To address the concern on fast metabolism, bufalin-PLGA microspheres (MS) were prepared via membrane emulsification to achieve prolonged pain-relief effects. western blotting, Real-time PCR, immune fluorescence and molecular docking were employed to demonstrate the therapeutic action of bufalin on NPP. Results showed enhanced thermal withdrawal latency (TWL) and mechanical withdrawal threshold (MWT) after the administration of both bufalin and bufalin-PLGA-MS to the CCI rats. Prolonged pain-relieving effects for up to 3 days with reduced dose frequency was achieved via bufalin-PLGA-MS. In the CCI rats treated with bufalin-PLGA-MS, the expression levels of protein and mRNA levels in TRPV1 and P2X7, both localized in the dorsal root ganglion (DRG), were reduced. Moreover, bufalin-PLGA-MS effectively reduced the levels of IL-1β, IL-18, IL-6 and TNF-α in the CCI group. The results from molecular docking suggested that possible mechanism of NPP alleviation of bufalin might through binding to P2X7 receptors directly. The administration of bufalin-PLGA-MS prepared by membrane emulsification demonstrated promising applications for sustained effect on the alleviation of NPP.